Clinical dilemmas in primary liver cancer - Williams, Roger (John Wiley & Sons, 2012)
Clinical Dilemmas in Liver Cancer follows the successful format of the other books in the Clinical Dilemmas series, with each chapter focused on a specific dilemma, or issue facing doctors in their day-to-day job, and providing them with practical clinical information and help to better assessment and treat their patients - in this case patients suffering from liver cancer, the third commonest cancer in terms of mortality worldwide. Chapters feature up-to-date information on the basic mechanisms, epidemiological risk factors, screening and surveillance strategies, diagnosis and treatment. It is.